Housing adaptability: Debate of current context (ARQUISUR Revista, 2020)
The Possibility of changing the activities and functions of housing spaces, as well as rearrange the layout, enables the dwell to move along with its user, transforming to suit different purposes. The implementation of simple and planned strategies, during the design phase, achieve a significant adaptability, reducing operating costs. The purpose of this research is to report the current context of housing adaptability, understanding how the theme is being treated in the scientific environment. We seek to understand if recent technologies and ways of living bring a new reflection on adaptability. To this end, were surveyed peer-reviewed international scientific publications from the 21st century in English language. Papers are divided according to the main topic, in order to cross-refer pertinent data and create a meaningful discussion contemporary. We note there is no consensus on the concept of adaptability, as well as a lack of advantages and disadvantages knowledge on design strategies. Among them are the costs, technologies, and social aspects, which represents a barrier to propagate adaptability. Therefore, conciliate construction professionals and their communication with clients is essential to disseminate adaptability.
Keywords: adaptability, construction, flexibility, habitat, technology